A nationwide cohort study of the incidence of microscopic colitis in Sweden. Issue 11 (15th April 2019) - Bergman, David; Clements, Mark S.; Khalili, Hamed; Agréus, Lars; Hultcrantz, Rolf; Ludvigsson, Jonas F.
Summary: Background: Epidemiological studies of microscopic colitis have shown varying but increasing incidence rates. Aim: To assess the incidence of microscopic colitis in Sweden. Methods: Nationwide cohort study performed in 1995‐2015 based on biopsy reports. Age‐specific and age‐standardised incidence rates were calculated. Results: We identified 13 844 patients with an incident diagnosis of microscopic colitis. Lymphocytic colitis (n = 9238) constituted 67% and collagenous colitis (n = 4606) 33% of microscopic colitis. The mean age at time of diagnosis of microscopic colitis was 60.2 years (58.6 for lymphocytic colitis, 63.3 for collagenous colitis). The lifetime risk of developing microscopic colitis was 0.87% in women (95% confidence interval, CI: 0.85‐0.88) and 0.35% in men (95% CI: 0.34‐0.36). From 2006, the overall incidence of microscopic colitis was approximately 10.5 cases per 100 000 person‐years (95% CI: 9.8‐11.3) with higher rates in women (72% of cases, incidence rate ratio = 2.4 (95% CI: 2.3‐2.5) and the elderly with increasing rates up to 75‐79 years. From 2006‐2015, there was a significant increase of 1% per year ( P = 0.02) in the overall microscopic colitis incidence rate in women; the estimated annual percent change was similar, although not statistically significant, in men ( P = 0.15). Conclusions: In Sweden, the incidence of microscopic colitis is still increasing in women, although the rate appears to be stabilising. The incidence is particularly high in women and the elderly up to age 75‐79 years. Finally, across a lifetime, 1 in 115 females and 1 in 286 males are expected to be diagnosed with microscopic colitis and thus posing a considerable disease burden.